CGIAR launches Digital Agriculture diploma to transform agri-food systems and rural communities in Latin America and the Caribbean - Ibabao, Xenina; Santiaguel, Alaric; Jiménez, Daniel (CGIAR System Organization, 2022)
The CGIAR Research Initiatives on Digital Innovation and AgriLAC Resiliente have collaborated with stakeholders to develop digital agriculture professionals in critical locations along the Central American Dry Corridor. A total of 26 agricultural professionals completed a new Digital Agriculture university diploma course, created to strengthen regional technical capacity in digital agriculture to enable better informed, data-driven decisions in agri-food systems.